1997
DOI: 10.1007/bf02900307
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and psychosocial consequences in depression of octo- and nonagenerians: results of an epidemiological study

Abstract: In a two-wave community study in Munich, Germany, a representative sample of 402 people older than 85 years was restudied 1 year later. In the first cross section a total of 358 (89.1%) subjects were interviewed. One year later 263 (73.5%) subjects were reexamined. Several diagnostic systems were used. The probands showed a high prevalence of depression--nearly one quarter of the interviewees. In this extreme age group gender differences in depression were minimal. Depressive were distinctly impaired in daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
4
18
1
Order By: Relevance
“…This also holds true for the oldest-old group (aged >75-90), for which several studies have found that physical (Forsell et al, 1998;Meller et al, 1997;Païvarintä et al, 1999) and cognitive functional impairment (Forsell et al, 1998) predict depression.…”
Section: Physical and Cognitive Functionmentioning
confidence: 59%
See 1 more Smart Citation
“…This also holds true for the oldest-old group (aged >75-90), for which several studies have found that physical (Forsell et al, 1998;Meller et al, 1997;Païvarintä et al, 1999) and cognitive functional impairment (Forsell et al, 1998) predict depression.…”
Section: Physical and Cognitive Functionmentioning
confidence: 59%
“…For example, in the longitudinal study by Jeon and Dunkle (2009), the oldest-old (aged >85) group was likely to report increased depressive symptoms with age. However, other studies have found a decline in the propensity for depression with increasing age (aged >65 years) (Mojtabai and Olfson, 2004) or no significant relationship with increasing age (aged >65 to >85 years) (Meller et al, 1997;Minicuci et al, 2002). Education level is also associated with depression.…”
Section: Socio-demographicmentioning
confidence: 94%
“…Whether older age is associated with depression continues to be controversial. Several studies have shown that depressive symptoms increase with age, while others have failed to find a relationship between depressive symptoms and age, or even found a decrease of depression with higher age . Therefore, it cannot be excluded that the correlation between depressive symptoms and female sex is independent of CP, and represents only an effect of sex and age.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that depressive symptoms increase with age, [55][56][57][58] while others have failed to find a relationship between depressive symptoms and age, or even found a decrease of depression with higher age. [59][60][61][62] Therefore, it cannot be excluded that the correlation between depressive symptoms and female sex is independent of CP, and represents only an effect of sex and age. Two studies found a correlation between arteriosclerosis and depression, particularly in women.…”
Section: Discussionmentioning
confidence: 99%
“…While institutionalisation concerns only a few people in the age group 50-60, it becomes increasingly relevant in the very old. A study in Munich found that, amongst the 80 and 90 year old population, more people living in nursing homes suffered from depression than those who did not [29]. Studies that exclude the institutionalised population, as most surveys do, may thus underestimate the prevalence of depression in late life.…”
Section: Discussionmentioning
confidence: 92%